Numerical model output data for publication "Control of the oceanic heat content of the Getz-Dotson Trough, Antarctica, by the Amundsen Sea Low" - Dotto, T. S.; Kimura, S.; Naveira Garabato, A. (Zenodo, 2020)
Contains MITgcm model output data to reproduce the analyses of the paper "Control of the oceanic heat content of the Getz-Dotson Trough, Antarctica, by the Amundsen Sea Low", by Dotto and co-authors, published inJournal of Geophysical Research-Oceans (doi:10.1029/2020JC016113). The model simulation is presented and described in Kimura et al. (2017; doi:10.1002/2017JC012926) and in Dotto et al. (2019; doi:10.1175/JPO-D-19-0064.s1).See the 'ReadMe.txt' file for a description of the data.